Active Aging in Very Old Age and the Relevance of Psychological Aspects - Paúl, Constança; Teixeira, Laetitia; Ribeiro, Oscar (Frontiers in Medicine, 2017)
Background: Active ageing encompasses a socially and individually designed mix of different domains that range from personal and familial, to social and professional. In being a key policy concept often focused on the young-old individuals, efforts in studying its dimensions in advanced ages have seldom been made. Nevertheless, there is a recognized need to promote adequate responses to the growing number of individuals reaching advanced ages, and to recognize their specific dependability on health-related aspects, services attendance, social interactions, or on psychological characteristics for what it means to “age actively”. Objective and Methods: This study provides a secondary analysis of data and follows the preceding work on the operationalization of the World Health Organization’s (WHO) Active Ageing model by means of an assessment protocol to measure which variables, within the model’s determinants, contribute the most for an active ageing process (Paúl, Ribeiro & Teixeira, 2012). Authors used the achieved model (composed by six factors: health, psychological component, cognitive performance, social relationships, biological component, and personality) and performed multi-group analysis of structural invariance to examine hypothetical differences between age groups (<75 years vs. ≥75 years), i.e., to test whether observed differences in the structural weights across age groups were statistically significant and to contrast obtained findings with the originally achieved model for the total sample (1322 individuals aged 55+). Results: Assuming an unconstrained model to be correct, the measurement weights for the two age groups were statistically different from one another; also, assuming the measurement weights to be correct, the structural covariances for the two age groups were statistically different from one another. The comparison of components between age groups revealed a major relevance of the psychological component for the older age group. Conclusion: These findings add evidence to the importance of psychological functioning in enabling an active commitment with later life, and the need for further research on specific psychological features underlying the subjective meaning of active ageing in more advanced ages.